ENTREPRENEURIAL INNOVATION AS A CATALYST FOR SUSTAINABLE DEVELOPMENT: A COMPREHENSIVE ANALYSIS OF SOUTH INDIAN STATES - Vijayabhasker Reddy (International Journal of Advances in Business and Management Research (IJABMR), 2025)
The intersection of entrepreneurship, fresh ideas, and long-term development results is now a major topic of research in modern economic writing. This study looks at how entrepreneurial ecosystems, especially those that help Micro, Small, and Medium Enterprises (MSMEs), affect the routes of sustainable development in six South Indian states. Using strict quantitative analysis, this study looks at the connection between entrepreneurship driven by innovation and metrics of sustainable development. The study employs a comparative method to divide states into two groups: high-performing and low-performing. This task is done using a set of composite metrics of sustainable development. The results demonstrate that there is a substantial positive correlation (r = 0.823) between MSME innovation skills and sustainable development scores. There are big variances in how well each state does. These states are 43% more innovative than those that do not perform as well. These findings add to the evidence that there is a connection between entrepreneurship and sustainability. They also provide policymakers suggestions for how to employ new business concepts to assist in reaching the goals of sustainable development.